The motivational basis of cognitive determinants of addictive behaviors. (May 2015) - Cox, W. Miles; Klinger, Eric; Fadardi, Javad S.
Abstract: If a person expects that (a) drinking alcohol or using another addictive substance will enhance positive affect or reduce negative affect, and (b) there is a strong likelihood that these desirable consequences will occur if the substance is used, that person is likely to form a goal of using the substance. The theoretical framework presented here predicts that when that happens, the person will have a current concern for using the substance, with the person thereby sensitized to environmental stimuli related to procuring and using the substance. One indication of the sensitization is selective attention to substance-related stimuli, which is correlated with urges to use and actual use of the substance. Accordingly, interventions have been developed for helping substance users to overcome substance-related attentional bias. The results are promising for reducing both the attentional bias and the substance use. Finally, we discuss other cognitive-modification and motivational techniques that have been evaluated with promising results. Highlights: Current concerns theory explains the cognitive basis for addictive behaviors. Having a substance-related goal sensitizes a person to substance-related stimuli. Substance-related selective attention is correlated with urges and actual use. Training reduces both substance-related attentional bias and substance use.